Are reports of memory failures in an understudied population of first-year female students related to self-confidence or anxiety? - Pilotti, Maura; Bo Julaia , Maryam; Aamir, Siddiqua (Journal of International Students, 2026)
The first year of college requires adjustments that are often described as cognitively and emotionally demanding, thereby potentially fostering symptoms of anxiety. It is particularly demanding for young female students (age range: 18-25) from a society emerging from patriarchy. Among this understudied population, the prevalence of symptoms of generalized anxiety disorder (GAD) is largely unknown. The present study examined the distribution of such symptoms, as well as the degree to which students subjectively perceived them as impairing academic and home activities and relationships (i.e., impact estimates). Then, students’ reports of prospective memory (PM) and retrospective memory (RM) slips were surveyed to determine the extent to which they could be differentially predicted by self-efficacy and GAD. Both prospective and retrospective memory slips increased with GAD symptomatology but were unrelated to either general or academic self-efficacy. T